Simulating vegetation shifts in north‐eastern Mediterranean mountain forests under climatic change scenarios - Nikolaos M. Fyllas; Andreas Y. Troumbis (Global Ecology and Biogeography, 2009)
Aim To explore potential shifts in vegetation and fire regime in some dominant forest types in the north‐eastern part of the Mediterranean basin under climate change. Location Two altitudinal gradients in the continental part of Greece. Methods We developed a forest gap dynamics simulator that provides feedback from the stand to its water balance and flammability status. The model is used to simulate vegetation dynamics in two mountainous areas, currently found under different aridity conditions. Two climatic change scenarios (Intergovernmental Panel on Climate Change A1 and B2) were applied to explore differences in the response of the established forest types. In addition we explicitly accounted for the role of fire, under both current and altered climate patterns. Results Fire was identified to play a significant role in low‐altitude sites. Its significance increased with the severity of the climate change scenario. Elevational shifts of the dominant species were simulated for each site, while in some cases these changes were associated with a shorter fire cycle and a frequent resetting of processes of vegetation change. Main conclusions Our simulations suggest a greater vulnerability of mountainous Mediterranean drier areas regarding compositional alteration and flammability trends. Changes in vegetation could take place through both a discrete and synergistic realization of changes in the drought stress and fire frequency.